Bolniki s sočasnimi boleznimi v družinski medicini - Petek Šter, Marija (Medicinski razgledi, 2008)
This review article deals with the problems of care of people with at least two chronic diseases, which is the definition of multimorbidity. Growing population of older people and better health care are the main reasons for higher number of multimorbid patients and they present the rule rather than anexception in family medicine. Multimorbidity is related to lower quality of life, psychosocial distress, more frequent hospitalisations, more complications of treatment, higher costs and higher mortality. Multimorbid patients more frequently seek for medical help, management of multimorbid patients takes more time, different chronic diseases which are present at the same time limit the use of results of clinical studies and guidelines, which usually deal with only one disease. Successful management of multimorbid patients takes a holistic approach, which is directed to the patient. This is one of the priorities of family medicine and keeps the family physician, whichis in a tight and long relationship with the patients, to the leading position in case of multimorbid patients.
Keywords: Družinska medicina; Family Practice; Comorbidity; Soobolevnost; chronic condition; Chronic Disease; Kronična bolezen; sočasne bolezni; kronične bolezni